2018
DOI: 10.1007/s12282-018-0853-9
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-6 receptor inhibitor suppresses bone metastases in a breast cancer cell line

Abstract: The results of the present study suggest that inhibition of IL-6 signaling may become a preventive therapeutic option for breast cancer and bone metastases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 38 publications
0
24
0
Order By: Relevance
“…With respect to its requirement for cell viability and growth, most tellingly, one group studying astrocytes (Quintana et al, 2013;Quintana et al, 2008) found that while global IL-6R knockout (which leads to compensations) had a small effect, conditional knockout in astrocytes led to their apoptosis. In support of the involvement of IL-6R in cell growth, other papers have linked IL-6 to intestinal epithelial cell and fibroblast growth, VEGF-A secretion from prostate cancer cells (Ishii et al, 2018), bone metastases in breast cancer (Wakabayashi et al, 2018) and hepatocyte proliferation. Additionally, IL-6R has been linked to increased gp130 expression and upregulation of leukemia inhibitory factor (LIF), an alternative gp-130 signaling system able to compensate for IL-6R deficiency Liu et al, 2000).…”
Section: Discussionmentioning
confidence: 95%
“…With respect to its requirement for cell viability and growth, most tellingly, one group studying astrocytes (Quintana et al, 2013;Quintana et al, 2008) found that while global IL-6R knockout (which leads to compensations) had a small effect, conditional knockout in astrocytes led to their apoptosis. In support of the involvement of IL-6R in cell growth, other papers have linked IL-6 to intestinal epithelial cell and fibroblast growth, VEGF-A secretion from prostate cancer cells (Ishii et al, 2018), bone metastases in breast cancer (Wakabayashi et al, 2018) and hepatocyte proliferation. Additionally, IL-6R has been linked to increased gp130 expression and upregulation of leukemia inhibitory factor (LIF), an alternative gp-130 signaling system able to compensate for IL-6R deficiency Liu et al, 2000).…”
Section: Discussionmentioning
confidence: 95%
“…Recently, Wakabayashi et al suggested that inhibition of IL-6 signaling may become a preventive therapeutic option for breast cancer and bone metastases [12].…”
Section: New Therapeutic Opportunities For Covid-19 Patients With Tocmentioning
confidence: 99%
“…The authors described a correlation between the presence of such signature and BM-free survival at 10 years (74% vs 83% in patients with high vs low gene expression levels, respectively; p = 0.048) [62] . Interestingly, a more recent study has showed that a monoclonal antibody against the human IL-6 receptor (Tocilizumab) reduced lytic BM development in a murine model of BC, by interfering with tumour cell proliferation, neoangiogenesis, and RANK signaling [63] .…”
Section: Application Of “Omics” Sciences To the Early Identification mentioning
confidence: 99%
“…Among these, MAF CNV as well as CAPG/GIPC1 and DOCK-4 over-expression in the primary tumour have been found to correlate not only with subsequent BM onset, but also with adjuvant zoledronate effectiveness [56] , [80] , [81] . Moreover, based on results of pre-clinical and clinical studies [59] , [60] , [61] , [62] , [63] , [72] , high intra-tumour levels of IL-1 β, IL-6 or miR-218-5p could not only provide prognostic information, but also potentially be targeted by novel therapeutic agents.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%